Blocking AGEs reduces airway epithelial viral susceptibility in diabetes-exacerbated COPD - Zhenfeng Chen; Yueying Qin; Bingqi Lin; Linle Jiang; Zhencheng Feng; Shiying Chen; Zuodong Ye; Min Zhou; Jia Li; De Yun Wang; Nanshan Zhong; Panpan Hou; et al. (EMBO Molecular Medicine, 2026)
Abstract Although diabetic complications are well-established in multiple organs, their impact on the respiratory system remains unclear. Clinical evidence indicates accelerated chronic obstructive pulmonary disease (COPD) progression in individuals with diabetes, yet the underlying mechanisms are poorly defined. Using single-cell RNA sequencing of airway epithelium, we identified distinct transcriptional alterations in COPD patients with or without diabetes, particularly in host–defense pathways related to viral infection, which is a key driver of COPD exacerbations. Functionally, hyperglycemia enhanced influenza virus susceptibility in both COPD-derived epithelial cells and COPD mice with diabetes, indicating compromised airway defense. We further demonstrated that hyperglycemia promotes advanced glycation end products (AGEs) accumulation in airway epithelium, with AGEs levels correlating with infection severity. Pharmacological inhibition of AGEs formation with aminoguanidine significantly reduced viral load both in vitro and in vivo. Mechanistically, AGEs activate p38/ERK/IKK proinflammatory signaling via RAGE and MD2 receptors, leading to epithelial injury and heightened viral susceptibility. Our findings reveal a hyperglycemia-AGEs-RAGE/MD2 axis that increases viral susceptibility in COPD, highlighting AGEs targeting as a promising therapeutic strategy for COPD patients with diabetes.